Microplastics in the atmosphere: Adsorb on leaves and their effects on the phyllosphere bacterial community - Libo Xu; Kang Li; Bai, Xinyi; Zhang, Guangbao; Tian, Xudong; Qian Tang; Mengjun Zhang; Min Hu; Yi Huang (Journal of Hazardous Materials, 2024)
Phyllosphere is the largest interface between the atmosphere and terrestrial ecosystems and serves as a major sink for atmospheric microplastics (MPs). It is also a unique habitat for microbiota with diverse ecological functions. This field study investigated the characteristics of atmospheric MPs adsorbed on leaves with automatic technology, and found their abundance was 3.62 ± 1.29 items cm−2. MPs on leaves were mainly below 80 µm, and dominated by polyamide, polyethene, and rubber. MPs on leaves correlated significantly with the structure and functions of the phyllosphere bacterial community (PBC). Both the MPs abundance and size distribution (MSD) were positively correlated with the α diversity and negatively correlated with the β diversity and network complexity of PBC. PBC functions of environmental and genetic information process were negatively correlated with MPs abundance, and functions related to human diseases and cellular process were positively correlated with MSD significantly. The relative abundance of Sphingomonas was significantly correlated with the MSD, suggesting that Sphingomonas might emerge as the key genus involved in the pathogenicity of PBC mediated by MPs. These results highlighted the ecological health risks of atmospheric MPs as they can be transferred anywhere and potentially increase the pathogenicity of local phyllosphere microflora.
Keywords: Allergenic microorganisms; Atmospheric microplastics; Bacterial community; Microplastic distribution characteristics; Phyllosphere